Tecnologias da informação e comunicação na educação: conceitos e definições - Geraldi, Luciana Maura Aquaroni; Bizelli, José Luís (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
Information and communication technologies (ICT) bring new ways and knowledge of production methods in the school environment. Technological innovations allow to improve the relationship School / Teacher; teacher / student and student / student. Therefore, it is necessary to understand the use of digital tools and their results. The text presented here analyzes the relevant literature to the theme of ways of working and put ICT in the classroom setting. The prospect of the proposed approach shows the importance of investments in access and literacy for the use of innovations, starting with the formation of educators able to review their teaching methods and practices.